Bank Specific Factors, Macroeconomic Variables and Market value of Nepalese Commercial Banks - Paudel, Ramesh (INTELLIGENCE Journal of Multidisciplinary Research, 2024)
The present research has been carried out to identify the relationship and impact of bank specific factors, macroeconomic variables on the market value of Nepalese commercial banks. This research is based on descriptive cum causal research design with quantitative data from secondary sources. The study adopts panel regression to capture both cross sectional and longitudinal data characteristics and employs ordinary least square model with 120 observations of 20 commercial banks as entire population from the period of 2016/17 to 2021/22. The study reveals that banks with higher loan growth and size tend to maintain efficient market value, yet careful lending areas selection are crucial to mitigate no performing loan risk, which can decrease profitability and increase market risk. Higher non-interest income to non-interest expenses, operating revenue to operating expenses are major dimension to increase the market value. Book value per share and dividend payout ratio reflecting investor confidence in the bank’s net worth and consistence return. The banks might adopt the strategy of diversifying lending portfolio, introduce non-interest income generation program along with increases the size and operation of the activities. The bank could follow the policy of increasing cash and stock dividend through higher profit. The study focuses on selected bank specific and macroeconomic factors without considering fixed/random and structural model. Future studies aim to employ in identifying causal link between bank factors, service quality and market value with different panel data model.